Information Processing and Technical Knowledge Contribute to Self-Controlled Video Feedback for Children Learning the Snatch Movement in Weightlifting. Issue 4 (August 2021) - Souissi, Mohamed Abdelkader; Souissi, Hichem; Elghoul, Yousri; Masmoudi, Liwa; Trabelsi, Omar; Ammar, Achraf; Chtourou, Hamdi; Souissi, Nizar
Our aim in this study was to examine, via technical performance analysis and speed of execution, whether information processing and technical knowledge help explain learning benefits of self-controlled video feedback in children's weightlifting performance. We randomized 24 children (aged 10 to 12 years) into self-controlled (SC) and yoked (YK) feedback groups. Learners underwent test sessions one week before (pre-test) and one day after (post-test) six weightlifting training sessions. During each test session, we recorded kinematic parameters of snatch performance using Kinovea version 0.8.15 software. After the learning sessions, the SC group improved on most kinematic parameters (e.g., the horizontal displacement of the bar between the first and the second pulls [ M DXV = 25.42%, SD = 18.96, p = 0.003) and the maximum height reached by the bar ( M HMV = 5.51%, SD = 7.71, p < 0.05)], while the YK group improved only on the DxV ( M DXV = 19.08%, SD = 24.68, p < 0.05). In addition, the SC group showed a more advanced phase of cognitive processing compared to the YK group, and the SC group showed a superior improvement in their technical knowledge level ( p < 0.001) compared to the YK group ( p < 0.05). Thus, key elements to correcting motor errors in children's weightlifting through self-controlled feedback were improvements in information processing and technical knowledge.